Editorial. (13th November 2013) - Shinde, Vasant
Ancient Asia is the official annual journal of the Society of South Asian Archaeology (SOSAA). The Ancient Asia Editorial Board is pleased to present volume 4 of the journal of the Society of South Asian Archaeology to the scholarly world.